Strategy for Creating Characters Based on the Tolak Bala Ritual in the Theater Performance of Hideung Geulis Play - Intan Markamah (JOMANTARA, 2025)
Abstract Kawung trees in Banceuy Village are often tapped to obtain their sap. Before tapping, the tappers perform the Tolak Bala ritual to ward off potential misfortunes. This ritual activity serves as an idea for creating characters in theater performances. This study addresses the problem of the strategies of character creation based on the Tolak Bala ritual in the theater performance of the Hideung Geulis play. This study aimed to describe the creation of characters based on the Tolak Bala ritual. The approach employed in this study was the concept of reading literary reception as proposed by Wolfgang Iser. Methods of data collection included observation, interviews, and literature studies. The study results demonstrate the creation of characters through text (the Tolak Bala ritual). For example, the Kawung tree is depicted as a woman named Hideung Geulis. Monkeys and lizards, symbolic of nuisance, are portrayed as the characters of Momon and Karman, who act as thugs. The supernatural creature as nuisance is represented by the character of Santi with a bad character. The perpetrator of the ritual is depicted as a helpful character, while the tapper is characterized as a morally flawed individual. These characters collectively from the cast of the Hideung Geulis play. Keywords: Strategy, Character Creation, Tolak Bala Ritual, Kawung Tree, Hideung Geulis.